The Role Of Artificial Intelligence (ai) In The Mental Preparation Of High-level Athletes - HAFSAOUI, Benyoucef (Journal of Sport Science Technology and Physical Activities, 2025)
The Object of the study aims to identify the role and importance of artificial intelligence the mental preparation of high-level athletes. For this purpose, we used the method a descriptive and analytical approach, which is based on theoretical readings and publications related to psychological and mental preparation, as well as modern artificial intelligence tools used to develop athletes' performance. On this basis, the study recommended the necessity and importance of the psychological and mental preparation of the athlete, which has become an essential component of the modern training process, the inclusion of a sports psychologist and/or a mental trainer to manage the different psychological and mental states of athletes, and the organization of study days should be for coaches to teach them psychological and mental preparation techniques, and to introduce them to the different artificial intelligence devices and tools that contribute to the psychological and mental preparation of high-performance athletes.